Eremias papenfussi sp. nov., a new lacertid lizard (Sauria: Lacertidae) from Tehran Province, Iran - Mozaffari, Omid; Ahmadzadeh, Faraham; Parham, James F. (Zootaxa, 2011)
We describe a new species of Eremias lacertid from the Alborz Mountain range in northern Iran (Tehran Province). Eremias papenfussi n. sp. is part of the Eremias subgenus (or morphotype) by virtue of lacking lateral fringes on the fourth toe and color pattern. It can be further differentiated from previously described species assigned to this morphotype by the absence of distinctly keeled upper caudal scales, gular scales that do not extend to the second inframaxiallary scales, color pattern, and scale counts. Eremias papenfussi is found on rocky mountain slopes of the Alborz where it is presumed to have a much broader distribution than demonstrated by the available specimens. Of the 15 species of Eremias known from Iran, E. papenfussi is the fifth species known to inhabit rocky mountain slopes along with E. strauchi, E. lalezharica, E. montanus and E. novo.